A Novel CD40L Mutation Associated with X-Linked Hyper IgM Syndrome in a Chinese Family. (2nd April 2020) - Li, Liangshan; Ji, Jing; Han, Mengmeng; Xu, Yinglei; Zhang, Xiao; Liu, Wenmiao; Liu, Shiguo
ABSTRACT: Background : Mutations in CD40 ligand gene ( CD40L ) affecting immunoglobulin class-switch recombination and somatic hypermutation can result in X-Linked Hyper IgM Syndrome (HIGM1, XHIGM), a kind of rare serious primary immunodeficiency disease (PID) characterized by the deficiency of IgG, IgA and IgE and normal or increased serum concentrations of IgM. The objective of this study is to explain genotype-phenotype correlation and highlight the mutation responsible for a Chinese male patient with XHIGM. Methods : Whole exome sequencing (WES) and Sanger sequencing validation were performed to identify and validate the likely pathogenic mutation in the XHIGM family. Results : The results of the sequencing revealed that a new causative mutation in CD40L (c.714delT in exon 5, p.F238Lfs*4) which leads to the change in amino acids (translation terminates at the third position after the frameshift mutation) appeared in the proband. As his mother in the family was carrier with this heterozygous mutation, the hemizygous mutation in this patient came from his mother indicating that genetic mode of XHIGM is X-linked recessive inheritance. Conclusion : This study broadens our knowledge of the mutation in CD40L and lays a solid foundation for prenatal diagnosis and genetic counseling for the XHIGM family.